2011
DOI: 10.1021/es1025883
|View full text |Cite
|
Sign up to set email alerts
|

Determining Air−Water Exchange, Spatial and Temporal Trends of Freely Dissolved PAHs in an Urban Estuary Using Passive Polyethylene Samplers

Abstract: Passive polyethylene (PE) samplers were deployed at six locations within Narragansett Bay (RI, USA) to determine sources and trends of freely dissolved and gas-phase polycyclic aromatic hydrocarbons (PAHs) from May to November 2006. Freely dissolved aqueous concentrations of PAHs were dominated by fluoranthene, pyrene, and phenanthrene, at concentrations ranging from tens to thousands of pg/L. These were also the dominant PAHs in the gas phase, at hundreds to thousands of pg/m3. All stations mostly followed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 29 publications
10
56
0
Order By: Relevance
“…The R s of target PAHs ranged from 0.38 L d À1 (2,3,5-TNap in Heart Lake) to 120 L d À1 (BaA in Lake Reid) (Table S5), and slightly increased with increasing log K pew . This increasing trend was also observed for PAHs with PE samplers in Narragansett Bay, Rhode Island, USA (Lohmann et al, 2011). The errors of R s for individual analytes depend on the errors in the fitting parameters a and b, i.e., log R s-PRC ¼ a  log K pew þ b.…”
Section: Sampling Rates Of Target Analytessupporting
confidence: 54%
“…The R s of target PAHs ranged from 0.38 L d À1 (2,3,5-TNap in Heart Lake) to 120 L d À1 (BaA in Lake Reid) (Table S5), and slightly increased with increasing log K pew . This increasing trend was also observed for PAHs with PE samplers in Narragansett Bay, Rhode Island, USA (Lohmann et al, 2011). The errors of R s for individual analytes depend on the errors in the fitting parameters a and b, i.e., log R s-PRC ¼ a  log K pew þ b.…”
Section: Sampling Rates Of Target Analytessupporting
confidence: 54%
“…Less rainfall is associated with lower pollutant impact by wet deposition. As a matter of fact, dry deposits are highly polluted in urban atmosphere (Lohmann et al 2011). Bomboi and Hernandez (1991) (Yin et al 2011).…”
Section: Temporal Variationmentioning
confidence: 99%
“…Passive sampling allows for a direct measurement of freely dissolved and vapor phase concentrations, avoiding filter bias and providing a time-weighted average incorporating episodic events [23]. Several studies have demonstrated the use of passive samplers to measure the diffusive flux of PAHs across air-water interfaces [15,19,[24][25][26][27]. Fewer studies have utilized passive samplers to measure the diffusive flux of PAHs between porewater and water [28][29][30].…”
Section: Introductionmentioning
confidence: 99%